The Influence of Health Education Using Pocket Books on Mothers' Knowledge Level Regarding Stunting in Kasilib Village - Husnanisa Kusuma Wardani; Noor Yunida Triana; Ikit Netra Wirakhmi (LPPM Universitas Harapan Bangsa, 2023)
Stunting is a condition where toddlers have less height compared to their age. This study aims to determine the effect of health education using the pocketbook method on the level of knowledge of mothers about stunting in Kasilib Village. This research is quantitative, using the Pre-Experiment research type, using the One Group Pretest Posttest Design approach. The sampling technique used was the accidental sampling with a total sample of 132 mothers. The sample was taken by accidental sampling. The statistical test used in this study uses the Paired T-Test. The results of the study stated that most of the respondents had a high school education as many as 69 (52.3%), and most of the respondents did not work as many as 82 people (62.1%). The level of mother's knowledge before health education was carried out as many as 72 respondents (53.8%) had sufficient knowledge about stunting after health education was carried out as many as 95 respondents (72%) had good knowledge about stunting. The results of the Paired T-Test obtained a p-value of 0.000 <0.005, which means that there is an influence of health education using the pocketbook method on the level of knowledge of mothers about stunting in Kasilib village. Posyandu cadres or health workers in the working area of ​​Kasilib Village can conduct health education related to stunting regularly.